Smart Decision Systems in Healthcare Sustainability Toward Global Research Trends and Sustainability Strategy Implications - Tini Adiatma; Okto Irianto; Maria Enjelika Manik (Journal of International Conference Proceedings, 2026)
The rapid proliferation of smart decision systems within healthcare settings has emerged as a pivotal force in advancing global sustainability agendas, yet a comprehensive understanding of the field's intellectual trajectory remains elusive. This study employs a systematic bibliometric analysis that conducted through Biblioshiny using data retrieved from the Scopus database to map the evolving landscape of research at the intersection of smart decision systems, healthcare, and sustainability. The analysis encompasses publication trends, citation networks, co-authorship patterns, keyword co-occurrence structures, and the most influential contributing countries, institutions, and journals. Findings reveal a marked acceleration in scholarly output since 2018, with artificial intelligence, clinical decision support, and sustainable health systems constituting the dominant thematic clusters. Emerging research frontiers include the integration of machine learning into resource allocation frameworks and the application of Internet of Things technologies in sustainable hospital management. These results underscore the strategic significance of interdisciplinary collaboration and evidence-informed policy formulation. The study ultimately provides researchers, healthcare administrators, and policymakers with a data-driven roadmap for directing future investments and aligning smart health technologies with long-term sustainability goals.